Právní režim Arktidy (mezinárodněprávní aspekty režimu Severního ledového oceánu), srovnání s právním režimem Antarktidy - Huk Kloučková, Eliška (Univerzita Karlova, Právnická fakulta, 2024)
The main objective of this thesis is to analyse the legal regimes of the Arctic and Antarctica and to compare them. The research question is whether and in what specific ways the legal regimes of these polar regions differ. The thesis mainly uses the descriptive method, which describes the basic background and the applicable legal framework, and then the comparative method when comparing the two regimes. In addition to the introduction and conclusion, the thesis is divided into a total of seven chapters. The thesis thus first defines the Arctic and Antarctic, introduces their history and outlines their geopolitical significance. The main parts of the thesis are devoted to the legal regime. In the case of the Arctic, which is mainly a frozen sea around the North Pole, the law of the sea relevant to this territory is discussed. Attention is given to the 1982 UN Convention on the Law of the Sea and its application to the Arctic Ocean. The thesis also describes the pending disputes in this area and the challenges that this legal regime poses not only for Arctic states. In the case of Antarctica, which is a continent, the complex treaty regime that was treaty-anchored in 1954 is discussed. Attention is also paid to the European Union's interest in these areas, as well as the Czech Republic's. Hlavním cílem této práce je analýza právní režimu Arktidy, respektive Severního ledového oceánu, a Antarktidy a jejich následná komparace. Výzkumnou otázkou je, zda a v čem konkrétně se liší právní režimy těchto polárních oblastí. V práci je využito převážně metody deskriptivní, s jejíž pomocí jsou popsány základní východiska a platná právní úprava, a následně při porovnání obou režimů pak metoda komparativní. Kromě úvodu a závěru je práce je rozdělena do celkem sedmi kapitol, které jsou dále členěny. Práce tak nejprve definuje Arktidu a Antarktidu, představí jejich historii a nastíní geopolitický význam. Hlavní části práce jsou věnovány právnímu režimu. V případě Arktidy, která je převážně zamrzlým mořem kolem severního pólu, ...